Spinel Lifexco2-Xo4 0 25 ? X ? 1 as Cathodes in Lithium Batteries. Relationship Between Ionic Distribution and Lithium Ion Insertion - Ortiz-Farias, J; Ortiz-Farias, J; Gautier-Zamora, J; Gautier-Zamora, J; Pastene-Olivares, R; Pastene-Olivares, R; Herrera-Diaz, F; Herrera-Diaz, F; Alburquenque-Munoz, D; Alburquenque-Munoz, D (Sociedad Chilena de Quimica, 2013)
Spinel lifexco2-xo4 samples with ? x ? were synthesized by the sol-gel Pechini method at 300oC in order to study the impact on their structural and electrochemical properties due to the substitution of Co by Fe. The specific capacity for lithium insertion into the electrode materials depend on lithium diffusion coefficient DLi which in turn depends on the Fe3+/(Fe3++Co3+ +Co4+) octahedral cationic ratio.